A human right to friendship? Dignity, autonomy, and social deprivation. Issue 9 (21st October 2022) - Wittrock, Jon
ABSTRACT: The aim of this article is twofold: to interpret human dignity in terms of multidimensional autonomy, and to apply this conceptual framework to the question of a potential human right to friendship, addressing problems of social deprivation. Several objections to such a new human right are answered, including charges of indignity, conceptual redundancy, misleading terminology, feasibility (weak objections) rights intrusion, responsibility, tolerability, and illiberality (strong objections). A conceptual framework of autonomy is presented, dividing it into liberty (freedom from coercion) opportunity (available options to chose from) capacity (for an agent to act) and authenticity (information on the likely consequences of choices). Not all of these can be maximised simultaneously, and decisions on how to safeguard human dignity involve difficult trade-offs between them, as well as considerations on their extension across space, and over time. Finally, several potential public measures, aimed at alleviating social deprivation are presented, ranging from education, information, and social training, to access to transportation, and public gatherings at major holidays. These measures, it is argued, should be considered in relation to the multidimensional character of human autonomy, as well as the varying causes of social deprivation, and they should be proportional to the perceived extent of the problem.